(untitled) (Journal of the College of Education for Women, 2019)
Soils at Al-Koot-Btera were choosen to determine their sedimentaryenvironments. It is found that there are , five soil series and as mentioned :MF11-MW9-DM97-DM57-DF95 . The five found soil series are of internalwell drained ,moderate and imperfect. Their textures vary in moderately,fineand moderately fine.indicating that sediments rang from poorly to very poorly sorting. Values of mediandiameter Md Ø range between 4.11-7.80 Ø .The relation between the sortingand median diameter shows that 95.24% of samples is a sedimentaryenvironment of aquite river , while 4.76% is aeolian sediments.The values of meso to platy kurtic of most horizon materials rangbetween 0.67-1.26 Ø .That is to say the samples were exposed to the samesediment environment , and that only 4.76% of the whole samples with leptokurtic was exposed to different sediment environments.